Human Trafficking in Northeastern Ontario: Collaborative Responses - Nagy, Rosemary; Snooks, Gina; Quenneville, Brenda; Chen, Lanyan; Wiggins, Sydnee; Debassige, Donna; Joudin, Kathleen; Timms, Rebecca (First Peoples Child & Family Review, 2020)
Human trafficking for the purpose of sexual exploitation is undoubtedly occurring in Northeastern Ontario. However, there is a lack of information, resources, coordination, and collaboration on the issue in comparison to Southern Ontario. Furthermore, urban-based programming from “down south” does not necessarily fit the unique circumstances of Northeastern Ontario: specifically, the isolation and underservicing of rural and remote communities, the presence of francophone communities, and diverse Indigenous communities. The Northeastern Ontario Research Alliance on Human Trafficking is a community-university research partnership that takes a critical anti-human-trafficking approach. We combine Indigenous and feminist methodologies with participatory action research. In this paper, we first present findings from our eight participatory action research workshops with persons with lived experience and service providers in the region, where participants identified the needs of trafficked women and gaps and barriers to service provision. Second, in response to participants’ calls for collaboration, we have developed a Service Mapping Toolkit that is grounded in Indigenous cultural practices and teachings, where applicable, and in the agency and self-determination of persons experiencing violence, exploitation, or abuse in the sex trade. We conclude by recommending seven principles for building collaborative networks aimed at addressing violence in the sex trade. The Service Mapping Toolkit and collaborative principles may assist other rural or northern communities across the county.